أثر السلوك القيادي لمديري المدارس على أداء المعلمين من وجهة نظر المعلمين - كحول وفاء; عموري سليمة (My University, 2023)
هدفت هذه الدراسة المعنونة ب"أثر السلوك القيادي لدى مديري المدارس على المعلمين من وجهة نظر المعلمين" للكشف عن الفرضيات التالية: - توجد فروق دالة احصائيا بين متوسطات السلوك القيادي عند مديري المدارس من وجهة نظر المعلمين حسب متغير (الجنس, الشهادة العلمية, الخبرة, النقطة الادارية) - توجد فروق دالة احصائيا بين متوسطات الأداء الوظيفي حسب متغير (الجنس, الشهادة العلمية, الخبرة, النقطة الادارية) تم اجراء هذه الدراسة على عينة استطلاعية قوامها 30 معلما ومعلمة يمارسون مهنة يمارسون مهنة التدريس بابتدائية (المجاهد ذهب التجاني) في ولاية الوادي, تم اختيار عينة الدراسة الأساسية بطريقة عشوائية عنقودية، ولتحقيق أهداف الدراسة استخدمت الباحثة المنهج السببي المقارن,وتم الاعتماد على استبيانين الاول حول السلوك القيادي لمديري المدارس من وجهة نظر المعلمين، والثاني حول الاداء الوظيفي للمعلم.وقد تم التوصل الى: - انه لايوجد فروق ذات دالة احصائيا بين متوساطات السلوك القيادي حسب متغير (الجنس, الخبرة, المؤهل العلمي, والنقطة الادارية). - انه لايوجد فروق ذات دالة احصائيا بين متوساطات الاداء الوظيفي حسب متغير (الجنس, الخبرة, المؤهل العلمي, والنقطة الادارية). Summary of the study in English This study, entitled "The Impact of Leadership Behavior of School Principals on Teachers from the Teachers' Perspective," aimed to reveal the following hypotheses: - There are statistically significant differences between the averages of leadership behavior among school principals from the point of view of teachers according to the variable (gender, educational degree, experience, administrative point) - There are statistically significant differences between job performance averages according to the variable (gender, academic degree, experience, administrative point) This study was conducted on an exploratory sample of 30 teachers, male and female, practicing a profession practicing the profession of teaching in elementary school (Al-Mujahid Dahab Al-Tijani) in the state of El-Wadi. The leadership behavior of school principals from the teachers' point of view, and the second is about the teacher's job performance. It has been concluded: - There are no statistically significant differences between the medians of leadership behavior according to the variable (gender, experience, academic qualification, and administrative point). - There are no statistically significant differences between the medians of job performance according to the variable (gender, experience, academic qualification, and administrative point).
مذكرة ماستر في علم النفس تخصص علم النفس المدرسي
Keywords: القيادة; La conduite; Leadership; الأداء الوظيفي; Functionality; Fonctionnalité